PROFIL PREFERENSI MASYARAKAT PERKOTAAN DALAM BERWISATA - Abdillah A, Fitri; Bella, Bella; Setiawati, Lidya; Olivia, Vivi (Universitas Muhammadiyah Jember, 2019)
AbstractThis study identifies the factors that influence the tourists’ choice of destination and evaluates the preferences of tourists for destinations. The goal of this paper is to examine the specific preferences of Jakarta citizen in choosing a tourist destination. Descriptive method is used to describe the profile of urban communities in choosing destinations. A total of 94 respondents were selected using purposive sampling. The results showed that urban communities prefer to travel abroad with Japan as the main destination. OTA (Online Travel Agent) is the main choice for travelling abroad because the trps are usually done in groups so that the arrangement becomes more efficient. In increasing the preferences of people traveling inbpund of the country, it needs to collaborate between government and travel bureau to promote local destinations.